Pengukuran Kualitas Layanan Website Akademik Universitas Sriwijaya Kota Palembang Menggunakan Metode Webqual 4.0 dan Importance Performance Analysis (IPA) - Muhammad Fauzan Ahnaf; Hanifah Muslimah Az-Zahra; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
One of universities in Palembang city, Sriwijaya University, where the university has used a web-based information system to support the student's academic process. The application was realized in web media which was later better known as Unsri's academic. But sometimes the quality of service of a college website has not been able to meet the expectations of it's users, so in order to maintain or even improve the quality of services, a website must certainly get special attention. So the quality of universities in terms of website assessment is better. So from that quality improvement in website-based services is an effort that must be carried out continuously. This study was conducted to determine the value of service quality of the academic site Unsri from the user's preception using Webqual 4.0, find out the effect of usability variabels, information Quality, Service Interaction Quality and find out the Importance Performance Analysis (IPA) quadrant grouping on each webqual indicator. This research uses data collection techniques using questionnaires with a total sample of 117 respondents. The results of the IPA quadrant analysis indicate that there are five attributes that are the top priority in improvement, namely, attractive appearance, additional knowledge from website information, providing up to date information, providing sufficiently detailed information, and users feeling safe about their personal information. Furthermore, there are five attributes that are included in the low priority of improvement , namely ease of navigation, proper preparation of information, user feel safe to make transactions, website provide space for personalization, and websites make it easy to communicate with organizations. Other attributes do not have priority improvement because they are classified as quadrants that have sufficient service performance values to be maintained or even have excessive value.